Meanings at hand: Coordinating semiotic resources in explaining mathematical terms in classroom discourse. Issue 3 (1st September 2016) - Heller, Vivien
Abstract: The article examines how diverse semiotic resources are made available for explaining mathematical terms in a fifth-grade classroom. Situated within the methodological framework developed by conversation analysis and the analysis of embodiment-in-interaction, the study deals with two instances of a classroom episode in each of which participants establish a 'found object' (Streeck1996 ) as relevant to the interaction and transform it into an exemplar of a mathematical solid. The two episodes differ in terms of the participants' manipulatory access to the objects: in the first instance, the 'explainer', when textualising his explanation, has greater opportunities for organising semiotic resources himself; in the second instance, it is the recipient of the explanation who manipulates the object, thus requiring the explainer to adapt her use of semiotic resources to his actions. In comparing the two episodes, the study examines what opportunities the different organisational forms of coordinating semiotic resources entail for textualising explanations. Findings shed light on a) the relationship between speech and bodily and material semiotic resources at the discourse level and b) the distribution of semiotic resources in the particular context of the classroom.